1997
DOI: 10.1161/01.atv.17.4.748
|View full text |Cite
|
Sign up to set email alerts
|

Defects of Insulin Action on Fatty Acid and Carbohydrate Metabolism in Familial Combined Hyperlipidemia

Abstract: Familial combined hyperlipidemia (FCHL) is a common cause of premature myocardial infarction, but its metabolic basis is unknown. Insulin resistance has been suggested in some patients by the presence of fasting hyperinsulinemia. We studied insulin action on carbohydrate and fatty acid metabolism in FCHL patients and healthy control subjects by a two-step euglycemic, hyperinsulinemic clamp. During low-dose insulin infusion, steady-state nonesterified fatty acids (NEFAs) were higher in patients than in control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 42 publications
3
52
0
1
Order By: Relevance
“…This would increase gluconeogenesis, 51 reduce hepatic insulin extraction 52 and stimulate VLDL apolipoprotein B and TAG production. 53,54 Reduced insulin-mediated glucose uptake through the glucose-fatty acid cycle is also linked with elevated NEFA, 55 which would lead to glucose intolerance and hyperinsulinaemia. The data from the present study showed positive correlations between waist, subcutaneous fat mass, suprailiac skinfold thickness and NEFA concentrations in the Sikh men, and a positive association between suprailiac skinfold thickness and NEFA in the Caucasian men, thereby supporting the above hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This would increase gluconeogenesis, 51 reduce hepatic insulin extraction 52 and stimulate VLDL apolipoprotein B and TAG production. 53,54 Reduced insulin-mediated glucose uptake through the glucose-fatty acid cycle is also linked with elevated NEFA, 55 which would lead to glucose intolerance and hyperinsulinaemia. The data from the present study showed positive correlations between waist, subcutaneous fat mass, suprailiac skinfold thickness and NEFA concentrations in the Sikh men, and a positive association between suprailiac skinfold thickness and NEFA in the Caucasian men, thereby supporting the above hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance has been associated with most of the characteristic metabolic disorders in FCHL 6 (high triglyceride levels, combined hyperlipidemia, high apoB levels, hepatic overproduction of lipoproteins, and small LDL size), as well as with the disorder itself. 10,11 In addition to dyslipidemia, insulin resistance in these patients may also contribute to increased risk of atherosclerosis. 24,25 Therefore, studies on the mechanisms that could potentially cause both insulin resistance and dyslipidemia in these patients are of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Because most of the characteristic metabolic disorders in FCHL (high triglyceride levels, combined hyperlipidemia, high apoB levels, hepatic overproduction of lipoproteins, and small low density lipoprotein [LDL] size) also have been associated with insulin resistance, studies on insulin action in these patients are of great interest. 6 In previous studies hyperinsulinemia 7,8 and impaired insulin action on glucose metabolism and free fatty acid suppression have been associated with combined hyperlipidemia 9 and FCHL, 10,11 indicating that insulin resistance is an essential part of this disorder. Genetic defects that could explain a large part of either insulin resistance or FCHL itself have not yet been found.…”
Section: F Amilial Combined Hyperlipidemia (Fchl) Is Character-mentioning
confidence: 94%
See 2 more Smart Citations